Uncovering cortico-striatal correlates of cognitive fatigue in pediatric acquired brain disorder: Evidence from traumatic brain injury. (October 2016) - Ryan, Nicholas P.; Beauchamp, Miriam H.; Beare, Richard; Coleman, Lee; Ditchfield, Michael; Kean, Michael; Silk, Timothy J.; Genc, Sila; Catroppa, Cathy; Anderson, Vicki A.
Abstract: Cognitive fatigue is among the most profound and disabling sequelae of pediatric acquired brain disorders, however the neural correlates of these symptoms in children remains unexplored. One hypothesis suggests that cognitive fatigue may arise from dysfunction of cortico-striatal networks (CSNs) implicated in effort output and outcome valuation. Using pediatric traumatic brain injury (TBI) as a model, this study investigated (i) the sub-acute effect of brain injury on CSN volume; and (ii) potential relationships between cognitive fatigue and sub-acute volumetric abnormalities of the CSN. 3D T1 weighted magnetic resonance imaging sequences were acquired sub-acutely in 137 children (TBI: n  = 103; typically developing – TD children: n  = 34). 67 of the original 137 participants (49%) completed measures of cognitive fatigue and psychological functioning at 24-months post-injury. Results showed that compared to TD controls and children with milder injuries, children with severe TBI showed volumetric reductions in the overall CSN package, as well as regional gray matter volumetric change in cortical and subcortical regions of the CSN. Significantly greater cognitive fatigue in the TBI patients was associated with volumetric reductions in the CSN and its putative hub regions, even after adjusting for injury severity, socioeconomic status (SES) and depression. In the first study to evaluate prospective neuroanatomical correlates of cognitive fatigue in pediatric acquired brain disorder, these findings suggest that post-injury cognitive fatigue is related to structural abnormalities of cortico-striatal brain networks implicated in effort output and outcome valuation. Morphometric magnetic resonance imaging (MRI) may have potential to unlock early prognostic markers that may assist to identify children at elevated risk for cognitive fatigue post-TBI.